Developing digital literacy application for Extensive Listening materials - Khotim Maslikah; Utami Widiati; Anik Nunuk Wulyani; Tengku Intan Suzila Tengku Sharif (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
Learning resource transformation is essential in this digital era, and English teaching and learning is no exception, especially in Madrasah context. That is why providing digital Extensive Listening (EL) materials to promote comprehensible input and character values is needed. This study outlines how Muslim English Literacy (MEL) application was developed to support the digital transformation as an alternative for EL materials. Research and Development (R & D) design was executed comprising seven phases of needs assessment, product design and development, product validation, first round of product revision, field testing, second round of product revision, and final product dissemination. The results of the field testing and moderation suggest that the developed product, MEL, is practical and applicable in helping EFL students to get more language exposure so that their English language acquisition can be facilitated. In addition, the product integrating character values may also strengthen their identity of being Muslims. Further studies on similar material development with more various topics utilizing technology apps are worth conducting.Pengembangan aplikasi literasi digital untuk bahan ajar Extensive ListeningTransformasi bahan ajar sedang menjadi kebutuhan di era digital saat ini, termasuk dalam pembelajaran bahasa Inggris di Madrasah. Oleh sebab itu, ketersediaan bahan ajar Extensive Listening (EL) yang mengintegrasikan comprehensible input (i+1) atau ilmu pengetahuan dan nilai moral sangat dibutuhkan.  Artikel ini membahas bagaimana aplikasi Muslim English Literacy (MEL) dikembangkan untuk mendukung transformasi digital tersebut sebagai alternatif bahan ajar EL. Penelitian dan Pengembangan (R & D) ini diselesaikan melalui 7 tahap: analisa kebutuhan, desain dan pengembangan bahan ajar, validasi produk, revisi pertama produk, uji coba, revisi kedua produk, dan diseminasi produk akhir.  Hasil uji coba dan hasil akhir ini menunjukkan bahwa produk yang dikembangkan, MEL, bersifat praktikal dan diterapkan oleh para siswa dalam memperoleh lebih banyak pajanan bahasa Inggris sehingga mereka dapat meningkatkan kemampuan berbahasa Inggrisnya. Selain itu, produk ini juga bisa meningkatkan identitas mereka sebagai muslim dengan cara menerapkan nilai-nilai karakter yang diintegrasikan dalam produk ini. Selanjutnya, penelitian dan pengembangan semacam ini perlu dilakukan lagi dengan topik yang lebih beragam.